Management And Prevention Strategies For Non-Communicable Diseases (NCDS) And Their Risk Factors - Patnaik, Dr. Uttara; Saraswat, Mr Pravesh; Kumar, Sr Chandan (South Eastern European Journal of Public Health, 2025)
Non-Communicable Diseases (NCDs) such as cardiovascular diseases, diabetes, chronic respiratory diseases and cancer are becoming the foremost causes of morbidity and mortality during the recent decade. According to the World Health Organization (WHO), these diseases now kill a significant 71 per cent of people worldwide, constituting a huge public health problem. NCDs are on the rise and their increasing prevalence is closely associated with several modifiable risk factors — all of which represent the same public health challenges we strive to mitigate — such as tobacco use, unhealthy diets, physical inactivity, and excessive alcohol consumption. The risk factors related to these conditions are present in both high-income and low-income countries and contribute not only to the growing burden of disease but also to substantial economic costs such as health care costs and lost productivity.